Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1097/00001721-200109000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Internal jugular vein thrombosis following in-vitro fertilization in a woman with protein S deficiency and heterozygosity for the prothrombin 3′ UTR mutation, despite anticoagulation with heparin

Abstract: We report the case of a 31-year-old woman with protein S deficiency and heterozygosity for the prothrombin 3' UTR mutation who developed an internal jugular vein thrombosis despite therapeutic anticoagulation with a low molecular weight heparin, following in-vitro fertilization. This case indicates that the stimulus to thrombosis in such women is intense and can occur despite apparent therapeutic anticoagulation. Close attention should, therefore, be paid to any women with a personal or family history of throm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…Other identifiable risk factors (such as malignancy and use of central venous catheters) were reported in only three patients [36,59,63], all associated with venous thrombosis. For all but four patients (5%) [36,43,54,57], no thromboprophylaxis was administered during the treatment cycle; in 12 (13%) patients, at least low-dose thromboprophylaxis was given when OHSS developed and while the patients were hospitalized [23,37,[41][42][43]53,59,[79][80][81]. In six patients [51,55,57,62,63,81] with venous thromboses and in one patient with arterial thrombosis [72], progression of thrombosis occurred despite administration of anticoagulation; the overall risk of progression is 7.5%.…”
Section: Recent Findingsmentioning
confidence: 99%
“…Other identifiable risk factors (such as malignancy and use of central venous catheters) were reported in only three patients [36,59,63], all associated with venous thrombosis. For all but four patients (5%) [36,43,54,57], no thromboprophylaxis was administered during the treatment cycle; in 12 (13%) patients, at least low-dose thromboprophylaxis was given when OHSS developed and while the patients were hospitalized [23,37,[41][42][43]53,59,[79][80][81]. In six patients [51,55,57,62,63,81] with venous thromboses and in one patient with arterial thrombosis [72], progression of thrombosis occurred despite administration of anticoagulation; the overall risk of progression is 7.5%.…”
Section: Recent Findingsmentioning
confidence: 99%
“…Hereditary hypercoagulable states also increase the risk for thrombosis. Internal jugular vein thrombosis associated with OHSS has been described in association with factor V Leiden mutation (9), heterozygosity for both factor V Leiden mutation and prothrombin III 0 UTR mutation (10), activated protein C resistance (11,12), antithrombin III deficiency (13), and both protein S deficiency and heterozygosity for prothrombin III 0 UTR mutation (14). In addition to OHSS, our patient also had a hereditary hypercoagulable state, a positive lupus anticoagulant as another risk factor.…”
Section: Discussionmentioning
confidence: 65%
“…It was reported that other predisposing factors existed which increased the risk of thrombus, such as antithrombin III (11), activated protein C (12), protein S deficiency (13), and factor V mutation (14). In the present case, more specific thrombosis risk factors, such as protein C, protein S, Leiden V factor, and antithrombin III deficiencies, were not checked.…”
Section: Discussionmentioning
confidence: 75%